Treatment of intestinal helminthiasis: mebendazole only or mebendazole-pyrantel pamoate? - Wisman Dalimunthe; Charles Siregar; Munar Lubis; Syahril Pasaribu; Chairuddin P. Lubis (Indonesian Pediatric Society Publishing House, 2007)
Background Although intestinal helminthiasis causes high morbidity and has a negative impact on children's growth and development, the efficacy of antihelmintics for multiple helminthiasis in mass treatment is still doubtful. Objective To compare the efficacy of single dose mebendazole and a combination of pyrantel pamoate and mebendazole for the treatment of multiple infections due to Ascaris lumbricoides, hookworm, and Trichuris trichiura. Methods Subjects were elementary school students in Suka Village, Tiga Panah subdistrict, North Sumatera. They were randomized to either receive mebendazole (M Group) or mebendazole- pyrantel pamoate group (MP Group). Stool examinations were perfomed on each subjects on day 7, 14, 21, and 28 after treatment. Analyses were perfomed by using chi-squared and Mann-Whitney U tests. Results The prevalence of intestinal helminthiasis was 95.4%. T. trichiura (88.7%) was the most common cause of infection followed by A. lumbricoides (79.5%), and hookworm (3.1%). Two hundred thirty nine (76.8%) children had multiple infections. Although the egg reduction rate of intestinal helminthiasis in the combination group was faster than that of the mebendazole group, there was no significant difference in the cure rate of both groups. Conclusion A single dose of mebendazole is preferred for mass treatment of multiple intestinal helminthiasis infections.